A small push goes a long way: An evaluation of the cumulative effects of a cash transfer on South African youth - Jani, Tafadzwa (School of Economics, 2022)
Persistently high poverty rates in developing countries have negatively affected social welfare outcomes, including infant mortality, food security, life expectancy, and educational attainment. In the late 2010s, depressed household incomes endured in many developing countries in the Americas, Africa and Asia. Cash transfer programs were introduced in many low-income countries in the 1990s, often intended to reduce poverty and increase human capital. South Africa launched the child support grant (CSG) in 1998, an unconditional cash transfer for children below the age of seven. By 2017, the program boasted twelve million beneficiaries, with an upper age limit of eighteen. Globally, initial evaluations of cash transfers (including the CSG) focused on children, and the short-term impacts on education, health, and consumption. However, fewer evaluations of the impact of extended receipt have taken place, particularly using older beneficiaries who experience lifelong receipt. This thesis analyses the long-term effect of CSG receipt on youth outcomes. Observing a positive CSG effect on South African youth would be encouraging, given that 3.3 million youth were not involved in any employment, education, or training in 2018. The literature focussing on older youth outcomes and long-term receipt primarily examines educational outcomes, mainly evaluating cash transfer programs in North America. This thesis draws on the National Income Dynamics Survey, a nationally representative longitudinal study conducted in South Africa between 2008 and 2017. Both the irregular expansion pattern of the CSG, and the panel nature of the survey are utilised to estimate grant impact on two cumulative outcomes (educational achievement and physical health, measured by height), and two current outcomes (labour force participation and mental health), using a youth sample aged between fifteen and twenty-seven. Those experiencing a higher duration of CSG receipt display higher educational achievement, higher average height and lower labour force participation. However, no significant effects are found on mental health. These results suggest extended receipt of an unconditional transfer may positively impact human capital accumulation, while current outcomes are less likely to be affected (World Bank 2016).